Energy Storage Battery Systems Fundamentals and Applications - Haider, Sajjad; Haider, Adnan; Khodaei, Mehdi; Chen, Liang (IntechOpen, 2021)
This book examines the scientific and technical principles underpinning the major energy storage technologies, including lithium, redox flow, and regenerative batteries as well as bio-electrochemical processes. Over three sections, this volume discusses the significant advancements that have been achieved in the development of methods and materials for various storage systems. This book provides both beginners and professionals with a comprehensive introduction to the principles and applications of energy storage.